Direct identification of rat iNKT cells reveals remarkable similarities to human iNKT cells and a profound deficiency in LEW rats. Issue 2 (26th December 2012) - Monzon‐Casanova, Elisa; Paletta, Daniel; Starick, Lisa; Müller, Ingrid; Sant'Angelo, Derek B.; Pyz, Elwira; Herrmann, Thomas
<x xml:space="preserve">Abstract</x> iNKT cells are a particular lymphocyte population with potent immunomodulatory capa‐city; by promoting or suppressing immune responses against infections, tumors, and autoimmunity, iNKT cells are a promising target for immunotherapy. The hallmark of iNKT cells is the expression of a semiinvariant TCR (with an invariant α‐chain comprising AV14 and AJ18 gene segments), which recognizes glycolipids presented by CD1d. Here, we identified iNKT cells for the first time in the rat using rat CD1d‐dimers and PLZF staining. Importantly, in terms of frequencies (1.05% ± 0.52 SD of all intrahepatic αβ T cells), coreceptor expression and in vitro expansion features, iNKT cells from F344 inbred rats more closely resemble human iNKT cells than their mouse counterparts. In contrast, in LEW inbred rats, which are often used as models for organ‐specific autoimmune diseases, iNKT cell numbers are near or below the detection limit. Interestingly, the usage of members of the rat AV14 gene family differed between F344 and LEW inbred rats. In conclusion, the similarities between F344 rat and human iNKT cells and the nearly absent iNKT cells in LEW rats make the rat a promising animal model for the study of iNKT cell‐based therapies and of iNKT‐cell biology.